IMMUNOLOCALIZATION OF THE SMAD4 PROTEIN IN POSTNATAL PORCINE UTERUS - Yan Li; Quan-wei Wei; Jun-rong Li; Hubdar Ali Kaleri; Rui-hua Huang; Fang-xiong Shi (Journal of Animal and Plant Sciences, 2014)
Transforming growth factor beta (TGF-β) regulates a series of effects on biological events, including uterine morphogenesis. SMAD4, downstream signal protein of the TGF superfamily, is an essential factor for mediating the TGF-β superfamily signaling. In the current study, our objective was to investigate the localization and expression of SMAD4 in postnatal porcine uterus using immunohistochemistry to provide experimental clues illustrating the mechanism of TGF-β superfamily signaling during the process of uterine development. Our results revealed that SMAD4 was detected among all samples examined, and widely and differentially expressed in the uterine luminal and glandular epithelium, myometrium and stroma in different age groups. Our findings strongly suggested that TGF-β superfamily signaling may be involved in postnatal uterine development in pigs.
Keywords: SMAD4; TGF-β superfamily; Uterus; Pig